The Development of Reading Materials Based on Assamaturu Local Wisdom Using Heyzine Flipbooks Application to Improve the Reading Comprehension Skills of Fouth-Grade Students - Rahmat Satria Arafa; Sulfasyah Sulfasyah; Tarman Tarman (Universitas Muhammadiyah Enrekang, 2024)
This research focuses on developing reading materials based on local Assamaturu wisdom from Gowa Regency, South Sulawesi Province using the Heyzine Flipbooks application. Specifically, the research objective is to develop a prototype of reading material based on local Assamaturu wisdom using the Heyzine Flipbooks application and test the validity, practicality and effectiveness of the reading material developed. The development model used in this research is the 4-D development model (four D models). The stages of the 4-D model include defining, designing, developing and disseminating. Validity analysis was carried out by two expert experts. The validation results show that the research instrument is declared valid with a recapitulation value of 3.7. Furthermore, the results of the practicality analysis which came from questionnaire responses from teachers and students showed that reading materials based on local Assamaturu wisdom assisted by the Heyzine Flipbooks application were declared very practical with a presentation score of 92%. Effectiveness analysis based on reading comprehension test results shows that the average student score is 87 with a completeness presentation of 90%. This value is in the very good category. Thus, it can be concluded that the reading materials developed based on local Assamaturu wisdom with the help of the Heyzine Flipbooks application can be used to improve the reading comprehension skills of class IV students in elementary schools.